2012
DOI: 10.1080/00071668.2012.751523
|View full text |Cite
|
Sign up to set email alerts
|

The role of selenium in cadmium toxicity: interactions with essential and toxic elements

Abstract: 1. The study was part of a project designed to investigate if organic selenium (Se) can ameliorate the toxic effects of cadmium (Cd). The main objective of the present study was to investigate, in the chicken, the interactions between Se, Cd and the following elements: Sb, Ca, Cr, Co, Cu, Fe, Pb, Mg, Mn, Mo, Ni, V and Zn. 2. A total of 300 1-d-old chickens (broilers) were randomly distributed among 4 dietary treatments with 5 replicate pens per treatment. In T1, chickens were fed on a diet with 0·3 mg/kg added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
2
20
1
1
Order By: Relevance
“…The present study revealed that the concentrations of Cd, As, and V in breast muscle were significantly affected by the dietary treatments while the concentration of all other examined elements remained unaffected. The extend of increase of Cd level in breast muscle is in line with previous studies [16,17] indicating that breast muscle is a tissue that accumulates relative lower amounts of Cd compared to other nonedible tissues. Regarding the Cd level in breast muscle between the 2 treatments that had 50 ppm of added Cd in the diet, no statistically significant differences were noted.…”
Section: Discussionsupporting
confidence: 91%
“…The present study revealed that the concentrations of Cd, As, and V in breast muscle were significantly affected by the dietary treatments while the concentration of all other examined elements remained unaffected. The extend of increase of Cd level in breast muscle is in line with previous studies [16,17] indicating that breast muscle is a tissue that accumulates relative lower amounts of Cd compared to other nonedible tissues. Regarding the Cd level in breast muscle between the 2 treatments that had 50 ppm of added Cd in the diet, no statistically significant differences were noted.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, cadmium-induced cell death, while not inhibited, was also significantly reduced in RICTOR-silenced PC12 cells [31], highlighting the importance of this regulator in the context of heavy metal toxicity in the brain. In addition to rapamycin, selenium was also reported to antagonise cadmium induced toxicity; most likely also through effects on the important balance between pro-oxidant toxic metals and antioxidant essential elements [33,34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a role for iodothyronine deiodinase in catalyzing debromination of PBDEs in fish (Browne et al, 2009;Noyes et al, 2011); it may be that Pb can inhibit iodothyronine deiodinase activity via increasing oxidative damage (Chaurasia et al, 1996). Furthermore, iodothyronine deiodinase is a Se-containing enzyme with selenocysteine making up a critical component of the active site of deiodinase (St Germain and Galton, 1997;Köhrle, 2000) and studies indicate that competition between another heavy metal (Cd) and Se (Al-Waeli et al, 2012;El-Sharaky et al, 2007) is a possible mechanism involved in Cd-induced inhibition of iodothyronine deiodinase. Hence, it is plausible that increased Pb in fish might also inhibit iodothyronine deiodinase activity via competition between Pb and Se, which would lead to reduced BDE-209 metabolism, and fewer metabolic products of BDE-209.…”
Section: Discussionmentioning
confidence: 99%